The Implementation of the Glasser Learning Model to the Ability to Write the Poetry of Class IX Students of SMP Negeri 1 Raya Kahean in the New Normal Era - Mery Chris Isabella Saragih; Jubelando O Tambunan; Idawati Situmorang (Institute of Computer Science (IOCS), 2022)
The aims of this study was to determine whether there were significant differences in learning to write poem of students. This research was conducted in 2022 at SMP Negeri 1 raya Kahean.This is a quantitative research using an experimental approach and using the one group pretest-post test model. Furthermore, this research will be compared with the related-test sample at the significant level or the 0.05 level (95%). The result is pre-test mean value = 55.03 and post-test mean value = 86.83. from the data analysis, the research hypothesis was tested using the “t” test. From thr research results obtained tcount =27.31 with a significant level of 0.05 (95% confidence level) with df 29 obtained t table: 2.074. thus, if tcount > ttable, namely (27,31>2.074) then Ho is rejected, With Ho rejection, Ha is accepted. It can be concluded that the result of the ability to write the poem of students for the class IX grade of SMP Negeri 1 Raya Kahean are better after using the glasser method.